“Unnatural, unnatural, unnatural, unnatural unnatural” . . . but real? The Toolbox Murders (Dennis Donnelly, 1978) and the Exploitation of True Story Adaptations - Wickham Clayton (Transatlantica)
1970s horror film and exploitation staple, The Toolbox Murders (Dennis Donnelly, 1978), is here used as a case study in incoherent narrative strategy and ideology and explores the incoherencies of this relationship to adapting “true stories.” Through an overt intertitle, the film itself implicitly suggests that the events actually happened, listing specific years, current locations, and suggesting pseudonymous protection of the people involved. This comes at the conclusion of a film which contains a number of narratological incoherencies and ideological incongruities, as is typical of exploitation films of the period. Through engaging with Todd Berliner’s work on incoherent narration, along with theories of, and approaches to, true story adaptation, this article addresses not only how the film functions, but how it works as an adaptation of “actual events.” Furthermore, it addresses how The Toolbox Murders is positioned as an exploitation film. Apart from exploitative uses of sex and violence, this paper posits that the appropriation and use of claims to veracity is itself exploitative of both generic exploitation and the viewer’s cognitive reception of the closing intertitle trope. This article ultimately asserts that all of these elements work together to create a complex and unusual cinematic experience.